A rapid direct-differential agglutination assay for Brucella detection using antibodies conjugated with functionalized gold nanoparticles - Hans, Richa; Yadav, Pranjal Kumar; Zaman, M. Burhanuz; Poolla, Rajaram; Thavaselvam, Duraipandian (Frontiers in Nanotechnology, 2023)
Brucellosis is the most widespread and serious zoonotic disease worldwide which affects livestock, sylvatic wildlife, marine dwellers, and humans. It is acquired through Alphaproteobacteria which belong to the genus Brucella and is categorized as a potential bio-threat agent. In this study, we developed a rapid and direct differential whole cell (WC) agglutination-based assay for its on-field detection. The recombinant outer membrane (rOmp28) protein-derived specific mice IgG polyclonal antibodies (pAbs) of Brucella were purified using affinity chromatography and conjugated with functionalized gold nanoparticles (AuNPs) for rapid agglutination. A positive blot of 32 kDa protein revealed specific immuno-reactivity of rOmp28-pAbs using immunoblot analysis. For the synthesis of AuNPs, the conventional “Turkevich method” was optimized at a concentration < 1 mM of gold precursor for obtaining 50-nm-sized particles. Also, their physico-chemical characteristics were analyzed using UV-visible spectrophotometry, Fourier transform infra-red spectroscopy (FT-IR), Raman spectroscopy, X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), dynamic light scattering (DLS), zeta potential (ζ, ZP), and fluorescence spectroscopy. Furthermore, these AuNPs were functionalized with N-(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride (EDC) and N-hydroxysuccinimide (NHS) to prepare modified carboxylated AuNPs. For bioconjugation with Brucella rOmp28 IgG pAbs, antibody-conjugated functionalized AuNP constructs were prepared and characterized using FT-IR analysis with strong N–H deformations. Subsequently, these bioconjugated AuNPs were used to develop a direct-differential slide agglutination assay with a detection limit of 104 CFU mL−1. The sensitivity of this assay was compared with standard double-antibody sandwich ELISA (S-ELISA) using rOmp28 IgG pAbs with an LOD of 103 CFU mL−1 and a detection range of 102–108 CFU mL−1. No intraspecies cross-reactivity was observed based on evaluation of its specificity with a battery of closely related bacterial species. In conclusion, the increased sensitivity and specificity of the developed agglutination assay obtained using bioconjugated functionalized AuNPs is ≥ 98% for the detection of Brucella. Therefore, it can be used as an alternate rapid method of direct WC detection of bacteria as it is simple, robust, and cost-effective, with minimal time of reaction in the case of early disease diagnosis.